Model Pendampingan UMKM Santri sebagai Upaya Penguatan Ekonomi Kreatif di Pesantren Mawaridussalam - M. Guffar Harahap; Aswin Fahmi Darma (CV. BAROKAH PUBLISHER, 2025)
trengthening the creative economy within Islamic boarding schools (pesantren) is a strategic effort to promote students’ economic independence and institutional sustainability. Pesantren Mawaridussalam has considerable potential in developing student-based micro, small, and medium enterprises (MSMEs), yet these businesses have not been optimally managed, particularly in terms of business management, product innovation, and digital marketing. This community service program aimed to design and implement a mentoring model for student MSMEs through structured training, continuous assistance, and evaluation. The methods included needs assessment, entrepreneurship training, basic financial management guidance, branding enhancement, and optimization of digital marketing through social media and online marketplaces. The results indicate improved students’ understanding of business management, enhanced product packaging and brand identity, and expanded market reach, contributing to increased sales turnover. The mentoring model also fostered collaborative networks among students and pesantren management. Therefore, this model proves effective in strengthening a pesantren-based creative economy and supports the sustainable economic empowerment of students.